2020
DOI: 10.1089/trgh.2019.0059
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Experiences of Minority Stress for Transgender Women: Adaptation and Evaluation of Internalized and Anticipated Transgender Stigma Scales

Abstract: Purpose: Transgender women (TGW) experience high rates of stigma based on their gender identity. Research has documented how transgender stigma and other discrimination negatively contribute to health inequities, including higher rates of depression compared with the general population. However, few scales measuring transgender stigma exist, even fewer that specifically assess anticipated or internalized transgender stigma. We sought to validate an adapted transgender stigma scale in a diverse sample of TGW. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This includes perceived prejudice (perception of discrimination directed at them for being transgender), anticipated prejudice (expectation of rejection/discrimination for being transgender), “passing” concerns (desire to not appear to be a transgender person and/or seeking to have a gender expression similar to that of a cisgender person), among others [ 24 , 25 , 26 ]. The combination of the two sets of stressors leads to negative psychological outcomes, which are already well documented in the literature [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…This includes perceived prejudice (perception of discrimination directed at them for being transgender), anticipated prejudice (expectation of rejection/discrimination for being transgender), “passing” concerns (desire to not appear to be a transgender person and/or seeking to have a gender expression similar to that of a cisgender person), among others [ 24 , 25 , 26 ]. The combination of the two sets of stressors leads to negative psychological outcomes, which are already well documented in the literature [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, internalized transnegativity—sometimes referred to as internalized transphobia, internalized stigma, or gender identity self-stigma (e.g., Rendina et al, 2020; Testa et al, 2017; Timmins et al, 2017)—refers to a transgender person’s internalization of a negative attitude toward transgender people (Staples et al, 2018). So far, a few studies have shown that internalized transnegativity is associated with suicidality, depression, and social anxiety (Perez-Brumer et al, 2015; Testa et al, 2015; Testa et al, 2017).…”
mentioning
confidence: 99%
“…The third concern is the extent to which some research strategies may recreate or activate the traumatic or stigmatizing experiences they are designed to understand. Stigma and minority stress scales [ 38 , 39 , 40 , 41 ] often include items that can be experienced as stigmatizing in and of themselves (e.g. “Whenever I think of being transgender, I feel depressed;” “Most transgender people end up lonely and isolated;” “Being transgender is disgusting to me”) [ 40 ] or ask participants to recount and relive stigmatizing experiences (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma and minority stress scales [ 38 , 39 , 40 , 41 ] often include items that can be experienced as stigmatizing in and of themselves (e.g. “Whenever I think of being transgender, I feel depressed;” “Most transgender people end up lonely and isolated;” “Being transgender is disgusting to me”) [ 40 ] or ask participants to recount and relive stigmatizing experiences (e.g. history of physical and sexual violence, family rejection, incidents of discrimination and harassment) to document their association with negative affect or health behaviour [ 5 ].…”
Section: Discussionmentioning
confidence: 99%